Magnetic linear driving method for high-voltage direct current inspection robot. (17th June 2020) - Xu, Xian Jin; Chen, Hao Da; Yang, Zhi Yong; Hu, Shi Chao; Yan, Yu
Faced with the problem of frequent slippage of the wheel-arm inspection robot in overhead high-voltage transmission lines, a magnetic linear drive method, based on high-voltage direct current (HVDC) magnetic field, is proposed: The ampere force of an enhanced HVDC magnetic field, generated by an innovatively arranged current-carrying coil, is used as the driving force for the traction robot, replacing the traditional wheel-arm driving method, thereby eliminating the slip. A physical model for the magnetic driving force is established, according to the characteristics of the magnetic field around the HVDC transmission line and the driving force requirements of the robot. The relationship between the magnetic driving force, the physical model size, and the number of coil windings is analyzed. The magnetic drive model is simulated using the COMSOL software version is 5.0. The simulation results of the magnetic drive force model are compared to theoretical calculations, proving the proposed method as correct. The magnetic drive device is constructed according to the proposed magnetic drive model and experiments are carried out. The results show that the magnetic drive device can provide enough traction to drive the robot motion, proving that the proposed magnetic linear drive method is technically feasible.